Dofetilide for suppression of atrial fibrillation in hypertrophic cardiomyopathy: A case series and literature review. Issue 4 (12th March 2018) - Moore, JoEllyn C.; Trager, Lena; Anzia, Lucille E.; Saliba, Walid; Bassiouny, Mohamed; Bhargava, Mandeep; Chung, Mina; Desai, Milind; Garberich, Ross; Lever, Harry; Lindsay, Bruce D.; Sengupta, Jay; et al.
Abstract: Background: Limited medical options are available for rhythm control in patients with atrial fibrillation (AF) and hypertrophic cardiomyopathy (HCM). There are no published reports of dofetilide use in this population. Methods: A retrospective chart review was conducted on 1, 404 patients loaded on dofetilide for AF suppression at the Cleveland Clinic from 2008 to 2012, 25 of whom were found to have HCM. Results: The HCM cohort was 32% female, 76% with persistent AF, mean age of 59 ± 10 years, and mean ejection fraction of 54 ± 9 %. Of the 25 patients, 21 were discharged on dofetilide, three discontinued during loading due to QTc prolongation, and one due to inefficacy. There were no adverse events during loading. Of those discharged on dofetilide, 11/21 (52%) were still on it at a median follow‐up of 396 (198, 699) days at the time of the chart review. For those in whom it was discontinued, the median time on the drug was 301 (111, 738) days. Of the 10 patients who discontinued dofetilide during follow‐up, six were due to inefficacy, one postablation, one postheart transplant, one due to death secondary to lung cancer, and one due to worsening edema. Conclusions: Dofetilide was well tolerated in this group of patients with AF and HCM and it facilitated management of AF in 21/25 (84%) patients. Further research is needed to assess the safety and efficacy of dofetilide in order to develop evidence‐based guidelines for the pharmacological management of AF in this population.